Dampak Menggunakan Game Online terhadap Kreativitas Berpikir - Robino Indan; Harri Kurniawan (Jurnal KomtekInfo, 2021)
Online games at this time are not just free time fillers but have entered the category of necessity, along with technological developments and easy access to the internet making online games an entertainment that must be owned by students, teenagers, and even parents. The thinking of most people online games has a negative impact, online game addiction can make someone antipathy to the real environment, but behind the negative impact, there are several positive impacts generated by online games, namely players will get fast and creative ways of thinking that can be obtained. from strategy games, not only that players can also learn teamwork from gameplay. Online game players can take advantage of this hobby to open business opportunities such as YouTube, buying and selling assets in online game characters, to making their own online games. The sample collection technique in this study used a correlational method, the number of samples studied was 45 people consisting of 82% male and 18% female with the age of 40% under 20 years and 60% over 20 years. By analyzing the data using the Servqual method, the results of online games can increase creative thinking which has an impact on creativity in entrepreneurship.